Fenofibrate inhibits hypoxia‐inducible factor‐1 alpha and carbonic anhydrase expression through activation of AMP‐activated protein kinase/HO‐1/Sirt1 pathway in glioblastoma cells. Issue 12 (14th September 2021) - Lin, Chingju; Lai, Sheng‐Wei; Shen, Ching‐Kai; Chen, Chao‐Wei; Tsai, Cheng‐Fang; Liu, Yu‐Shu; Lu, Dah‐Yuu; Huang, Bor‐Ren
Abstract: Cancer and its associated conditions have significant impacts on public health at many levels worldwide, and cancer is the leading cause of death among adults. Peroxisome proliferator‐activated receptor α (PPARα)‐specific agonists, fibrates, have been approved by the Food and Drug Administration for managing hyperlipidemia. PPARα‐specific agonists exert anti‐cancer effects in many human cancer types, including glioblastoma (GBM). Recently, we have reported that the hypoxic state in GBM stabilizes hypoxia‐inducible factor‐1 alpha (HIF‐1α), thus contributing to tumor escape from immune surveillance by activating the expression of the pH‐regulating protein carbonic anhydrase IX (CA9). In this study, we aimed to study the regulatory effects of the PPARα agonist fibrate on the regulation of HIF‐1α expression and its downstream target protein in GBM. Our findings showed that fenofibrate is the high potency compound among the various fibrates that inhibit hypoxia‐induced HIF‐1α and CA9 expression in GBM. Moreover, fenofibrate‐inhibited HIF‐1α expression is mediated by HO‐1 activation in GBM cells through the AMP‐activated protein kinase (AMPK) pathway. In addition, fenofibrate‐enhanced HO‐1 upregulation activates SIRT1 and leads to subsequent accumulation of SIRT1 in the nucleus, which further promotes HIF‐1α deacetylation and inhibits CA9 expression. Using a protein synthesis inhibitor, cycloheximide, we also observed that fenofibrate inhibited HIF‐1α protein synthesis. In addition, the administration of the proteasome inhibitor MG132 showed that fenofibrate promoted HIF‐1α protein degradation in GBM. Hence, our results indicate that fenofibrate is a useful anti‐GBM agent that modulates hypoxia‐induced HIF‐1α expression through multiple cellular pathways.